The Use of Flower Writing Strategy on Students’ Writing Skills (A Quasi-Experimental Research Design at the Tenth-Grade of SMA Negeri 9 Gowa) - Faizah, Nurul; Nappu, Syamsiarna; Ardiana (PROJECT (Professional Journal of English Education), 2025)
The present research examines the effect of the Flower Writing Strategy on the writing skills of tenth-grade students at SMA Negeri 9 Gowa. Utilizing a quasi-experimental research method featuring a non-equivalent control group, the research featured 68 students separated into experimental and control groups. The experimental group received the treatment using the Flower Writing Strategy, while the control group used the Guided Writing Strategy. Pre-test and post-test data were gathered, and the paired sample t-test was used for analysis. The results showed a significant increase in the experimental group with an increase in the mean score from 61.47 to 74.12 (an increase of 20.57%), compared to the control group which increased from 57.50 to 68.97 (an increase of 19.94%). Using a p< 0.05 statistical analysis, the Flower Writing Strategy was found to have improved the writing ability of the students The results show that by using a methodical and ordered visual approach, the Flower Writing Strategy helps students to improve their writing skills.